One Scandinavian approach to management by objectives and results? - Kristiansen, Mads Bøge (Scandinavian Journal of Public Administration, 2016)
This article details a comparative study of Management By Objectives And Results (MBOR) in three different tasks, Prison and Probation Services, Food safety and Meteorology, in central government in the three Scandinavian countries, Denmark, Norway and Sweden. The article examines differences and similarities in the design and use of MBOR across the countries (within each of the different tasks), and within each of the three countries (across the three tasks). The empirical basis comprises case studies in nine agencies and their parent ministry, carried out in 2010-2011. The article shows a range of differences as well as similarities in MBOR across the countries and tasks studied. Important factors at state-level as well as agency level such as the political-administrative structure and the measurability of tasks affect the design and use of MBOR. Although patterns can be discerned, the patterns are now and then quite complex. The findings point to the importance of the national and organisational context in which MBOR is implemented. The implication hereof is, that it is important to consider how the specific context, in which a MBOR system is implemented, will affect the system, and which consequences it will have.